Resistance of Leishmania infantum to allopurinol is associated with chromosome and gene copy number variations including decrease in the S-adenosylmethionine synthetase (METK) gene copy number. Issue 3 (December 2018) - Yasur-Landau, Daniel; Jaffe, Charles L.; David, Lior; Doron-Faigenboim, Adi; Baneth, Gad
Abstract: Leishmania infantum is one of the causative agents of visceral leishmaniasis (VL), a widespread, life-threatening disease. This parasite is responsible for the majority of human VL cases in Brazil, the Middle East, China, Central Asia and the Mediterranean basin. Its main reservoir are domestic dogs which, similar to human patients, may develop severe visceral disease and die if not treated. The drug allopurinol is used for the long-term maintenance of dogs with canine leishmaniasis. Following our report of allopurinol resistance in treated relapsed dogs, we investigated the mechanisms and markers of resistance to this drug. Whole genome sequencing (WGS) of clinical resistant and susceptible strains, and laboratory induced resistant parasites, was carried out in order to detect genetic changes associated with resistance. Significant gene copy number variation (CNV) was found between resistant and susceptible isolates at several loci, including a locus on chromosome 30 containing the genes LinJ.30.3550 through LinJ.30.3580 . A reduction in copy number for LinJ.30.3560, encoding the S-adenosylmethionine synthetase ( METK) gene, was found in two resistant clinical isolates and four induced resistant clonal strains. Using quantitative real time PCR, this reduction in METK copy number was also found in three additional resistant clinical isolates. Furthermore, inhibition of S-adenosylmethionine synthetase encoded by the METK gene in allopurinol susceptible strains resulted in increased allopurinol resistance, confirming its role in resistance to allopurinol. In conclusion, this study identified genetic changes associated with L. infantum resistance to allopurinol and the reduction in METK copy number identified may serve as a marker for resistance in dogs, and reduced protein activity correlated with increased allopurinol resistance. Graphical abstract: Distribution of relative quantity values (RQ) of gene LinJ.30.3560 from the 20 L . infantum clinical strains in relation to their allopurinol IC50 .Image 1 Highlights: Allopurinol resistance was previously described in L. infantum isolated from dogs. This study aimed at defining the genetic differences between susceptible and resistant strains. Gene and chromosome copy numbers differed between susceptible and resistant L. infantum strains. Decrease in METK gene copies was associated with increased allopurinol resistance. Inhibition of the enzyme encoded by METK increased allopurinol resistance.